2002
DOI: 10.3137/ao.400104
|View full text |Cite
|
Sign up to set email alerts
|

Lightning occurrence patterns over Canada and adjacent United States from lightning detection network observations

Abstract: IntroductionContinuous real-time coverage of lightning occurrence across southern Canada has been available since the installation of the Canadian portion of the integrated North American Lightning Detection Network (NALDN) was completed in February 1998. The Canadian Lightning Detection Network (CLDN) consists of 82 sensors that detect lightning over most of Canada to approximately 65°N in the far west, 55°N in the far east, and offshore to about 300 km. Previous information on lightning occurrence was availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 11 publications
3
51
0
Order By: Relevance
“…Finally, high numbers of lightning strikes associated with this system were detected by the Canadian Lightning Detection Network (Burrows et al, 2002). Thunderstorms were observed at The Pas between 07:00 and 09:00 UTC, and a total rainfall of 11.4 mm was recorded during this event.…”
Section: Evidence Of Precipitationmentioning
confidence: 99%
“…Finally, high numbers of lightning strikes associated with this system were detected by the Canadian Lightning Detection Network (Burrows et al, 2002). Thunderstorms were observed at The Pas between 07:00 and 09:00 UTC, and a total rainfall of 11.4 mm was recorded during this event.…”
Section: Evidence Of Precipitationmentioning
confidence: 99%
“…This goal has been achieved for a peak current threshold of 5 kA (Burrows et al, 2002). The network functions with 83 sensors distributed across the country, employing both Magnetic Direction Finding (MDF) and Time of Arrival (TOA) technologies; as of August 2009, it was composed of 27 IMPACT-ES, 30 LPATS-IV, 25 LS7000, and 1 LS7001 Vaisala sensors (Steve Kowalczyk, personal communication, August 2009).…”
Section: Description Of the Cldnmentioning
confidence: 99%
“…Although such regional lightning detection networks exist in many parts of the world and provide real-time data (e.g., Cummins et al, 1998b;Burrows et al, 2002;Cummins and Murphy, 2009;Höller et al, 2009;Lagouvardos et al, 2009), they generally provide limited spatial coverage, typically ending near national boundaries, and are unable to provide lightning data over the ocean. Lightning detection instruments also exist on orbiting satellites, such as the Optical Transient Detector (OTD; Christian et al, 2003) and the Lightning Imaging Sensor (LIS; Mach et al, 2007), however they are not able to provide continuous global coverage for all points on the Earth's surface.…”
Section: Introductionmentioning
confidence: 99%
“…July is the most active month for thunderstorm activity in central Alberta (Burrows et al, 2002;Kozak, 1998). According to Alberta Forestry lightning maps, thunderstorms were observed in the study area on all but two days in July 2000.…”
Section: A Daily Variation and Relative Cumulative Frequency Distribumentioning
confidence: 99%
“…A prime candidate for such a preliminary severe thunderstorm analysis, using RAPID, is the Carvel radar (53.34°N, 114.09°W) located near Edmonton, Alberta. Central Alberta is susceptible to frequent summertime convection (Burrows et al, 2002), and an average of 20 severe hail days are reported there each summer (Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%